Spectroscopy of nonequilibrium electrons and phonons - Shank, C. V. (Charles V.) (Modern problems in condensed matter sciences, 1992)
The physics of nonequilibrium electrons and phonons in semiconductors is an important branch of fundamental physics that has many practical applications, especially in the development of ultrafast and ultrasmall semiconductor devices. This volume is devoted to different trends in the field which are presently at the forefront of research. Special attention is paid to the ultrafast relaxation processes in bulk semiconductors and two-dimensional semiconductor structures, and to their study by different spectroscopic methods, both pulsed and steady-state. The evolution of energy and space distribution of nonequilibrium electrons and the relaxation kinetics of hot carriers and phonons are considered under various conditions such as temperature, doping and pumping intensity by leading experts in the field.